Effects of preserving juvenile rainbow trout (Oncorhynchus mykiss) in formalin and alcohol on body length, mass, and condition factor estimates - Greszkiewicz Martyna; Fey Dariusz P. (Fisheries & Aquatic Life)
Body length and weight are key parameters measured to provide information about the growth and condition of larval, juvenile, and adult fishes from both the wild and aquaculture. The goal of this study was to evaluate the effects of preservation in formalin and alcohol on juvenile rainbow trout, Oncorhynchus mykiss (Walbaum) standard body length (SL) and weight changes. Standard length (19.43–32.98 mm SL) decreased after 60 days of preservation by an average of 2.98% in 96% alcohol and 2.26% in 10% formalin. In contrast, fish body weight (0.094–0.63 g) decreased in alcohol (31.22%) but increased in formalin (11.65%). These percentage values can be used as correction factors, with the exception of fish body weight in alcohol since the size of individuals affected the magnitude of change. Accordingly, a correction formula accounting for fish weight must be applied (fresh weight (g) = -0.0363 + 1.667 × preserved length). Changes in fish length and body weight in different preservatives resulted in significant differences in the Fulton condition factor, with underestimation in alcohol (fresh F = 1.58; preserved F = 1.20) and overestimation in formalin (fresh F = 1.60; preserved F = 1.92).